Matrix stiffness determines the fate of nucleus pulposus–derived stem cells. (May 2015) - Navaro, Yosi; Bleich-Kimelman, Nadav; Hazanov, Lena; Mironi-Harpaz, Iris; Shachaf, Yonatan; Garty, Shai; Smith, Yoav; Pelled, Gadi; Gazit, Dan; Seliktar, Dror; Gazit, Zulma
Abstract: Intervertebral disc (IVD) degeneration and consequent low-back pain present a major medical challenge. Nucleus pulposus–derived stem cells (NP–SCs) may lead to a novel therapy for this severe disease. It was recently shown that survival and function of mature NP cells are regulated in part by tissue stiffness. We hypothesized that modification of matrix stiffness will influence the ability of cultured NP-SCs to proliferate, survive, and differentiate into mature NP cells. NP-SCs were subcultured in three-dimensional matrices of varying degrees of stiffness as measured by the material's shear storage modulus. Cell survival, activity, and rate of differentiation toward the chondrogenic or osteogenic lineage were analyzed. NP-SCs were found to proliferate and differentiate in all matrices, irrespective of matrix stiffness. However, matrices with a low shear storage modulus (G′ = 1 kPa) promoted significantly more proliferation and chondrogenic differentiation, whereas matrices with a high modulus (G′ = 2 kPa) promoted osteogenic differentiation. Imaging performed via confocal and scanning electron microscopes validated cell survival and highlighted stiffness-dependent cell-matrix interactions. These results underscore the effect of the matrix modulus on the fate of NP-SCs. This research may facilitate elucidation of the complex cross-talk between NP-SCs and their surrounding matrix in healthy as well as pathological conditions.